I motivi decorativi del duecento nei mosaici di San Marco a Venezia - Valenti, Devis (Hortus Artium Medievalium, 2014)
Abstract By the end of the twelfth century the mosaic decoration in the basilica of San Marco in Venice was completed. After the demolition of the galleries (late twelfth or early thirteenth century) the walls which became visible were decorated with mosaics during the first decades of the thirteenth century. Only a part of these mosaics is preserved today. However it is possible to notice the intention to make the new cycles homogeneous with the previous ones. Several decorative patterns are used in order to make these thirteenth-century additions coherent and better connected to the more ancient mosaics. This ornamental repertoire partly recuperates patterns already used in the basilica and partly introduces new typologies of frames.